Avaliação de diferentes protocolos de expansão rápida maxilar assistida cirurgicamente sobre o posicionamento mandibular: revisão sistemática da literatura e estudo em tomografias computadorizadas de feixe cônico com análise bidimensional e tridimensional - Carvalho, Francisco Samuel Rodrigues (2019)
Transverse maxilla deficiency is a dentofacial deformity characterized by the presence of posterior crossbite and several treatment modalities have been used in the treatment of this deformity. In adults or patients with established bone maturity, surgically assisted rapid maxillary expansion (SARME) has been indicated due to its predictability and lower associated morbidity. Despite the wide use of this treatment, there is no consensus in the literature regarding the need to perform pterygoid disjunction (PD). Thus, the present thesis consists of two chapters that aim, respectively: 1) to carry out a systematic review of the literature based on PROSPERO to evaluate whether the SARME associated with PD promotes changes in mandibular positioning; 2) to evaluate the occurrence of sagittal and/or vertical changes resulting from the use of SARME combined or not with PD. In Chapter 1, we proceeded with the systematic review of two phases, registered in the PROSPERO database. Nine databases were searched, including the gray literature. The 4 studies included a total of 142 adults and used images to perform linear measurements (pre and postoperative). The main outcomes evaluated were maxillomandibular transverse index (difference between mandibular width - distance measures between left and right antagonist points and maxillary width), sagittal (forward and backward) and vertical (impaction and extrusion) changes, dental exposure, chin projection and altered mandibular position. In chapter 2, the effect of SARME combined or not with PD on the value of sagittal and vertical measurements from cone beam computer tomography (CBCT) was analyzed. An observational, retrospective, analytical study was performed with 24 healthy individuals aged 18-45 years, with skeletal transverse maxillary deficiency greater than 5 mm, who underwent SARME (with or without PD) and who were observed at different times. For this, the computational processing of the CBCT images included: 1) tomographic alignment of the individual's head positioning through the ITK-SNAP and 3D Slicer; 2) cephalometric analysis of McNamara and Steiner-Tweed-Wits through the Dolphin Imaging 2D®; 3) three-dimensional shape matching analysis through the 3D Slicer. As conclusions, we have: (1) in the light of our knowledge this is the first work that makes an inferential analysis, not only descriptive, of the colorimetric analysis and relates it with alterations in cephalometric reconstructions and three-dimensional analysis, besides correlating findings of two-dimensional with threedimensional evaluations; (2) both protocols present similar dental and bone changes in both groups; (3) the variables related to the dental inclinations are more evident in the group without PD and the bone changes more evident in the PD group; (4) the possible effects of sagittal and vertical changes in the maxillomandibular complex should be considered in the preoperative period in order to avoid undesirable outcomes that may lead to aesthetic or functional impairment, (5) patients should be given a personalized treatment, according to the characteristics of their deformity; (6) future trials using threedimensional analyzes are required.